(Re)tracing queerness: archiving indentureship's 'coolie homo/erotic'. Issue 4 (2nd October 2019) - Wahab, Amar
Abstract : The erotic lifeworld of Indian indentureship remains buried. This visual essay probes the 'coolie homoerotic' as a creative reflection on the place of the homoerotic and queerness within the trans-oceanic lifeworld of coolie indentureship. It uses the methodology of visual assemblage to creatively and critically engage with a rare archival record of alleged sodomy on a coolie ship, the Mersey, bound for British Guiana from Calcutta in 1898. The author uses the archival document, as a residue of homoerotic possibility, to re-trace and deliberately reconfigure the historically present narrative of indentureship through a seven-image collection entitled Postcards from the Perineum. In critically responding to Victorian imagery of moral-labour discipline, the postcards were produced using techniques such as photography, sketching, painting, crafting and body printing. The aim is to visually and imaginatively open up a space for contemplating an aesthetic-eroto-political field of knowledge production in relation to the violence and indignities of indentureship. In doing so, the essay also suggests that indentureship is a site of contrapuntal queerness, through which we might critically provoke normative understandings of this term.